Randomized Clinical Trial Examining the Impact of Lactobacillus rhamnosus GG Probiotic Supplementation on Cognitive Functioning in Middle-aged and Older Adults - Sanborn V (Dove Medical Press, 2020)
Victoria Sanborn,1 M Andrea Azcarate-Peril,2 John Updegraff,1 Lisa Manderino,1 John Gunstad1,3 1Department of Psychological Sciences, Kent State University, Kent, OH, USA; 2Department of Cell Biology and Physiology and Microbiome Core Facility, UNC School of Medicine, Chapel Hill, North Carolina, USA; 3Brain Health Research Institute, Kent State University, Kent, OH, USACorrespondence: Victoria SanbornKent State University, Kent, OH, USATel +1 508-344-3215Fax +1 330-672-3786Email vsanborn@kent.eduPurpose: The gut microbiome has been linked to cognitive function and appears to worsen with aging. Probiotic supplementation has been found to improve the health of the gut microbiome. As such, it is possible that probiotic supplementation may protect the aging brain. The current study examined the cognitive benefits of probiotic supplementation (Lactobacillus rhamnosus GG) in healthy middle-aged and older adults.Materials and Methods: The study was a double-blind, placebo-controlled, randomized clinical trial. Two hundred community-dwelling adults aged 52– 75 were enrolled (mean age=64.3, SD=5.52). A three-month intervention involved daily consumption of probiotic or placebo. Independent sample t-tests, chi-squared tests, and repeated measure ANOVAs compared groups and examined changes over time. Primary outcome was change in NIH Toolbox Total Cognition Score from baseline to follow-up.Results: A total of 145 participants were examined in primary analyses (probiotic=77, placebo=68) and excluded persons due to discontinuation, low adherence, missing data, or outlier values. Established criteria (ie ≥ 1 subtest t-scores ≤ 35; n=19, n=23) were used to operationally define cognitive impairment. Repeated measures ANOVAs revealed that persons with cognitive impairment who consumed probiotics exhibited a greater total cognition score improvement than persons with cognitive impairment in the placebo group and cognitively intact persons in probiotic or placebo groups.Conclusion: Lactobacillus rhamnosus GG probiotic supplementation was associated with improved cognitive performance in middle-aged and older adults with cognitive impairment. Probiotic supplementation may be a novel method for protecting cognitive health in aging.Keywords: cognitive aging, dementia, microbiota, gastrointestinal microbiome, probiotics